The Foundations of a Realistic "Scientific" Theory of International Relations: from "Human nature" to International "Anarchy" - Adila, Mohamed Tahar (Journal of Legal Studies and Researches, 2021)
This study examines the Foundations that Realists require to build a Scientific Theory of International Relations. Starting from their perception of the Science, which is based on adopting the Principles of Positivism in its view of how to study Social and Human Phenomena, and ending with following the rules of the experimental approach that is based on observing the events (Phenomena) of International Reality and extracting what is considered constant and central to it. This can be translated into the concept of Power, which finds its justification in Human Nature for Morgenthau, and in the Anarchy of the International Order for Kenneth Waltz.